Mangrove ghost forests provide opportunities for seagrass - Twomey, Alice J.; Staples, Timothy L.; Remmerswaal, Amelia; Wuppukondur, Ananth; Lovelock, Catherine E. (Frontiers in Climate, 2023)
Mangrove forests are degraded by extreme climatic events worldwide, often leaving behind dead standing stems called ‘ghost forests’. Ghost forests may provide opportunities for seagrass colonisation but there is limited research into the conditions found within these ecosystems, or whether they provide a suitable habitat for seagrasses. This study aimed to characterise the environmental conditions within mangrove ghost forests, determine whether conditions are suitable for seagrass survival, and identify whether seagrass was present within the ghost forests of Moreton Bay, Queensland. Six study locations within mangrove ghost forests adjacent to live mangrove forests and seagrass meadows were selected and biophysical conditions within these habitats over the six sites were assessed. Two of the six study sites were found to have live seagrass present within the ghost forests (Godwin Beach and South Stradbroke). Suitable water temperature was linked to the presence and abundance of seagrass within mangrove ghost forests. Mangrove characteristics, including canopy cover, diameter at breast height, and stem densities, contributed to variation in the environment among the three habitats, suggesting that light is a key factor limiting seagrass colonisation into live or ghost mangrove forests. Overall, these results suggest that ghost forests can provide suitable habitats for seagrasses, and degraded mangroves may transition to seagrass under future sea level rise scenarios.